The role of CuCl on the mechanism of dibenzo-p-dioxin formation from poly-chlorophenol precursors: A computational study. (February 2016) - Fernández Pulido, Yoana; Suárez, Ernesto; López, Ramón; Menéndez, M. Isabel
Abstract: A computational study is performed for the elucidation of the role played by CuCl in the condensation of two polychlorophenol molecules to yield PCDDs. The mechanism found consists of six sequential steps, which allow the final recuperation of the CuCl molecule, and applies for phenol molecules with an ortho chlorine. In the temperature range of 453–473 K (previously reported as adequate to diminish PCDDs formation in the post-combustion area), CuCl is able to softly retain chlorophenol molecules, mainly those less chlorinated. After a first HCl release, Cu(I) remains bonded to phenol oxygen atom, thus avoiding the formation of phenoxy radicals and the subsequent radical processes. A temperature raise up to 1200 K destabilizes the initial CuCl-chlorophenol complexes and causes that the rate limiting step change from the formation of the first oxygen bridge to HCl elimination. It has been checked that tetra and penta-chlorophenols undergo essentially the same reaction process of 2-chlorophenol. In view of our results and trying to arrive at a practical way to diminish the rate of formation of PCDDs, we propose that an extra addition of powdered CuCl to the post-combustion zone, cooled down to temperatures lower than 473 K, could act as an inhibitor in the formation of these pollutants. Graphical abstract: Highlights: Molecular mechanism for the condensation of polychlorinated phenols with CuCl. CuCl avoids the formation of phenoxy radicals and any subsequent radical process. Addition of powdered CuCl to the postcombustion zone slows down formation of PCDDs.